The relationship between screen exposure and the increase in headache rates: a narrative review - Ferreira, Vinícius Salimos; Roza, Milena Kawana; Santos, Mariangela Beatriz Hoisler dos; Pinto , Paula Rafaella Teixeira Barbosa; GONCALVES, YASMIM SILVEIRA (Headache Medicine, 2024)
Introduction: Over the years, there has been a noticeable increase in the daily use of electronic devices among citizens. Due to the new lifestyle adopted by the population, various health consequences have emerged, among which the increase in the incidence of headaches is one of the most noticeable. The possibility that headaches related to screen use can impair health is a current reality with impacts and damages aren’t yet fully understood, making it essential to study the relationship between them in greater depth. Objective: To correlate high exposure to electronic device screens with the onset of headaches. Method: This is a narrative review conducted in the Medline database via PubMed and SciELO databases using the descriptors “headache”, "headache disorders", “computer”, "smartphone", “cellphone” and “screen time” between 2019 and 2024 in English. Results: A direct relationship was observed between screen exposure time and higher rates of headaches, as individuals who reduced their use of digital devices showed a decrease in headache occurrences. Individuals exposed to screens for 4 to 6 hours daily are the most affected group. An exacerbating factor for increased screen time was the COVID-19 pandemic, which induced greater use of electronic devices due to online classes and remote work. The brightness and frequency of the light were the factors that most impacted the occurrence of headaches. Age group is correlated with the risk of headaches, with adults being more affected compared to children; however, the age at which exposure to digital devices begins is also a significant factor. Conclusion: A strong correlation between screen exposure and a higher incidence of headaches was commonly observed among the researched articles. The main factors triggering this increase include longer exposure time, brightness and frequency of the light, age at which exposure to digital devices begins, and the user's age. These findings demonstrate the importance of the subject matter and highlight the urgency of further studies to understand the long-term health impacts on individuals.